Silent Pauses in the Speech of Yemeni EFL Learners - Abeer Mohammed Al-Ghazali; Yasser Alrefaee (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
Speaking fluently is characterized not only by the speed of oral delivery but also by the absence of non-fluent pauses. This paper aims at investigating the pausing phenomena in the speech of the Yemeni learners of English. It investigated three aspects of silent pauses, the frequency, the placement and the length.  The data were collected from 20 level four students enrolled in the Department English Language, Faculty of Education, Taiz University. The participants were recorded narrating the events of a short silent video immediately after watching it. Data were analyzed quantitatively utilizing the waveform spectrogram software called PRAAT. The findings showed that the Yemeni EFL learners overused non-fluent silent pauses. Additionally, they paused in the middle of the clauses rather than at the clause boundaries. With respect to the mean length of silent pauses, the speech of the EFL learners at Taiz University was full of long silent pauses which took one-third of the total speaking time. Therefore, it is highly suggested that the teachers of English should draw the learners’ attention to the notion of pausing and its effect on speaking fluency in order to lessen or avoid it. Teachers should also vary their activities to help the learners speak fluently without much pausing.